Nationwide Report on the Findings of Integrated School Health Screening Program in Iran - P Poursafa; P Mirmoghtadaee; H Ziaoddini; G Ardalan; T Aminaie; M Dashti; SM Alavian; MA Amirkhani; R Kelishadi (Tehran University of Medical Sciences, 2010)
Background: Screening of students´ health problems could lead to timely prevention and control of many health disorders. This study aimed to determine the nationwide prevalence of common disorders through school health screening program in Iran Methods: This cross-sectional national screening program was conducted in 2007-2008 among first- and third-grade- students in primary schools, first- grade-students of middle and high schools of all provinces in Iran.Results: Data were obtained from 3,124,021 (81.9%) students reported from the whole country classified into 33 geographical zones. Of total students studied, 12.48% had weight abnormalities, 4.77% had visual disorders, 3.95 % had head lice, 2.24% had behavioral disorders, and 0.6% had hearing disorders. Among students studied, 0.4%, 0.7%, 0.4% and0.8% had endocrine, psychological, neurological and genitourinary disorders, respectively. In addition, 2.1%, 1.9%, 1.8%, 0.8%0.5%, 0.3% and 0.3% of students had ear, nose & pharynx disorder, anemia ,skin & hair , cardiac ,abdominal, vertebral and lung problems, respectively. In elementary schools;57.6% of first-grade- students with at least one disorder were managed in outpatient settings and 6% of them were hospitalized for more investigation. Among third- grade- students of elementary schools, these values corresponded to 13.2% and 1.1%, respectively. Among first grade students of middle and high schools, this prevalence was 58.5% and 44.6% and 1.2% and 0.3% of students were hospitalized for more investigation.Conclusion: This integrated school screening program revealed a considerably high prevalence of health disorders among school students. These results might help health policy makers to design future health promoting programs.